Anti-biofilm Effect of β-Lapachone and Lapachol Oxime Against Isolates of Staphylococcus aureus - Fernandes, Antônio Wilton Cavalcante; dos Anjos Santos, Victória Laysna; Araújo, Cleônia Roberta Melo; de Oliveira, Helinando Pequeno; da Costa, Mateus Matiuzzi (Current microbiology, 2020)
Antimicrobial resistance in bacteria, such as Staphylococcus aureus , has been the subject of many assistance studies of alternatives for the treatment of infections. These studies aim to solve this problem for bacteria, such as biofilm formation. Aiming to control the emergence of the problem or enhance antibiotic activity, the data sources are inserted into new therapeutic alternatives for the treatment of infections. β-Lapachone and Lapachol Oxime are semi-synthetic derivatives of Lapachol with antimicrobial potential. Clinical isolates from human blood cultures were used in this study. Scanning electron microscopy (SEM) was performed following the glutaraldehyde fixation protocol. The presence of β-Lapachone and Lapachol Oxima interfered in the biofilm formation state. In the MEV, the effect was observed in the reduction of the population of biofilm-forming cells. Therefore, it was possible to conclude the promising potential of the anti-biofilm of substances, justifying the nature of the natural products as agents of inspiration for the detection of new compounds with the biological function.